Odpowiedź :
(2x-1)²= 4x^2-4x+1
(2-3x)²=4-12x+9x^2
(3x²-5)²=9x^4-30x^2+25
^ - oznacza operator do potęgi
(2-3x)²=4-12x+9x^2
(3x²-5)²=9x^4-30x^2+25
^ - oznacza operator do potęgi
(2x-1)²=2x²-4x+1
Δ=b²-4ac
Δ=(-4)²-4×2×1
Δ=16-8=4
(2-3x)²=4-12x+9x²=9x²-12x+4
Δ=b²-4ac
Δ=(-12)²-4×9×4
Δ=144-144=0
(3x²-5)²= 9x⁴-30x²-25 tego nie wiem jak doprowadzić do delty
Δ=b²-4ac
Δ=(-4)²-4×2×1
Δ=16-8=4
(2-3x)²=4-12x+9x²=9x²-12x+4
Δ=b²-4ac
Δ=(-12)²-4×9×4
Δ=144-144=0
(3x²-5)²= 9x⁴-30x²-25 tego nie wiem jak doprowadzić do delty
(2x-1)²=4xdo potegi2+1
(2-3x)²=4+9xdo potegi2
(3x²-5)²=9xdo potegi4+25
(2-3x)²=4+9xdo potegi2
(3x²-5)²=9xdo potegi4+25